If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 12 = 4x + 10 Reorder the terms: 12 + 5x = 4x + 10 Reorder the terms: 12 + 5x = 10 + 4x Solving 12 + 5x = 10 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 12 + 5x + -4x = 10 + 4x + -4x Combine like terms: 5x + -4x = 1x 12 + 1x = 10 + 4x + -4x Combine like terms: 4x + -4x = 0 12 + 1x = 10 + 0 12 + 1x = 10 Add '-12' to each side of the equation. 12 + -12 + 1x = 10 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = 10 + -12 1x = 10 + -12 Combine like terms: 10 + -12 = -2 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2
| 4m(-5m)(-6m)= | | 8*cos^2(x)-8*cos^4(x)=1 | | 16x-6=10x+30 | | x^2=3y^2+7z^2 | | 49x+10=12 | | sqrt(x^2+7x-44)=0 | | 5x+2y=130 | | 5(3-z)=2+1 | | sqrt(x^2+7x-44)=1 | | 4x-7=1+5x | | 2[4+6x-2]=36x+20 | | 2x^2-25x+33=0 | | 2ax+4bx= | | 15.5z-15.33=12.99+17.1z | | -78=-5/9(f-32) | | -8+5x+12=19x | | 7x-(2x+3)=9x-47 | | 3x+9+70+5x+27=180 | | X^2-12x+36=z^2 | | 2(x+.20)=3x-1.10 | | 4a+11=60-2 | | 2(x+.20)=3-1.10 | | 104-67=211(x-14) | | x+(x+.20)=3.50 | | -2x-13=7x-(2x-8) | | 4-3x=7x+8 | | 6(x+2)-36=4x+6 | | -2(n-5)-(3n-1)=-5+(4n-1) | | 2d-12=9+3 | | 8y+15=8y-40 | | 7x+5=2x-35 | | 12x+1144=24 |